Raw Materials, Profits, and the Productivity Slowdown: A Complementary Note - Bruno, Michael (Quarterly Journal of Economics, 1986)
Journal Article Raw Materials, Profits, and the Productivity Slowdown: A Complementary Note Get access Michael Bruno Michael Bruno The Hebrew University of Jerusalem Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 101, Issue 1, February 1986, Pages 197–200, https://doi.org/10.2307/1884649 Published: 01 February 1986